(untitled) (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: This study investigated the prevalence of Listeria monocytogenes in retail poultry shops, characterized the antibiotic resistance profile, and detected the genotypic pattern of virulence genes. Materials and Methods: Broiler meat (n = 90), intestinal content (n = 40), and environmental samples (n = 95) were collected for this study. Besides, hand swabs (n = 20) were obtained from the poultry shop workers and stool samples (n = 40) were collected from the outpatient clinics of Beni-Suef University Hospital, Egypt. The samples were subjected to isolation and identification of L. monocytogenes by conventional bacteriological examinations and biochemical tests, followed by confirmatory identification by the polymerase chain reaction. Results: Among the collected samples (n = 285), L. monocytogenes could be detected in 14.4% (n = 41/285) of the samples, where 30.0% (n = 12/40) of the intestinal content was positive. Similarly, 10.0% (n = 9/90), 15.0% (n = 3/20), and 12.5% (n = 5/40) of the samples of meat, hand swabs, and stools were found positive for L. monocytogenes, respectively. A total of 12 (12.6%) out of 95 environmental samples were positive for L. monocytogenes. Based on the antimicrobial sensitivity profile, most of the recovered isolates were multidrug-resistant against most commonly used antibiotics. Conclusion: The findings conclude that poultry shops play a vital role in transmitting L. monocytogenes to the consumers. Asymptomatic poultry shop workers should draw attention to their potentials for spreading the infection to the consumers through the contaminated carcasses. Low hygienic standards are present in commercial poultry shops that increase the risk of contamination in the sold products. J. Adv. Vet. Anim. Res., 7(4): 710-717, Dec 2020 http://doi.org/10.5455/javar.2020.g472